Eficiência energética em iluminação pública na gestão sustentável de cidades: estudo de multicasos - Salvia, Amanda Lange (2016)
The population growth and the concern with the use of natural resources make the sustainable cities theme increasingly addressed. One of its topics is energy efficiency, which amongst various applications, includes the public lighting service, which typically represents 3 to 4% of the electricity consumed by cities. Taking the importance and functions of this service into account, including public safety, quality of life and cities appreciation, sustainable management is necessary, considering economic, environmental and social aspects. In this context, the objective of this study is to investigate proposals for improving energy efficiency in public lighting of the municipalities of Rio Grande do Sul, in regards to its sustainable management. The methodology consists of five steps, starting with the presentation of energy efficiency indicators, and then the diagnosis of public lighting sustainability in three studied municipalities: Passo Fundo, Porto Alegre and Santa Maria. Such diagnosis was made by means of quantitative and qualitative indicators. Next, the best practices in the management of public lighting are presented, references in Brazil and in the world, according to research in online database, government pages and institutions that study the subject. After the search, it was possible to assess the applicability of these practices, using the multi-criteria analysis method Analytic Hierarchy Process (AHP), considering implementation cost, energy savings and ease of implementation as criteria. Finally, the step of presenting the suggested practices for each municipality, in order to contribute to its sustainable management, discussing the challenges and advantages of its possible implementation. The result of the diagnosis of public lighting sectors shows positive and negative aspects of the current situation, being able to relate higher energy consumption of the sector with lower percentages of LED bulbs. The multi-criteria analysis indicates the Retrofit Program as best practice to Passo Fundo, the Audit and Guide and Retrofit Programs to Porto Alegre and Alternative Energy and Management Programs to Santa Maria. This work contributed to the suggestion of alternatives to improve the energy efficiency of cities as well as discussed the main advantages and challenges of a possible implementation.